Toxic Productivity Among College Students: A Human Resource Management Perspective on the Early Formation of Work Behavior - Putri Sujani; Mutiara Trisnawati; Muhamad Pahlawan; Chandra Arifianto; Ivander Reinaldo Nantung (Fakultas Bisnis - Institut Bio Scientia International Indonesia, 2026)
This study aims to explore how toxic productivity is experienced by college students and to examine its implications from a Human Resource Management (HRM) perspective, particularly as an early formation of future work behavior. A qualitative phenomenological approach was employed through in-depth interviews with 15 university students, and the data were analyzed using thematic analysis. The findings reveal that students internalize productivity as a core component of self-worth, leading to persistent pressure to remain productive and feelings of guilt when resting. Academic demands and digitally mediated social comparison further reinforce this behavior, intensifying psychological strain. Toxic productivity manifests in emotional exhaustion, reduced motivation, and decreased wellbeing, indicating a potential risk for the development of maladaptive work patterns. In addition, ambivalent coping strategies were identified, where students attempted to rest but remained cognitively preoccupied with productivity demands, limiting effective recovery. From an HRM perspective, this study extends the Job Demands–Resources framework by highlighting the early internalization of productivity norms and their implications for workforce sustainability. The findings emphasize the importance of integrating well-being-oriented strategies in higher education to support sustainable human resource development.